Predictive Value of Left Atrial and Ventricular Strain for the Detection of Atrial Fibrillation in Patients With Cryptogenic Stroke - Bufano, Gabriella; Radico, Francesco; D'Angelo, Carolina; Pierfelice, Francesca; De Angelis, Maria Vittoria; Faustino, Massimiliano; Pierdomenico, Sante Donato; Gallina, Sabina; Renda, Giulia (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims Cryptogenic stroke (CS) is associated with a high rate of recurrences and adverse outcomes at long-term follow-up, especially due to its unknown etiology that often leads to ineffective secondary prevention. Asymptomatic atrial fibrillation (AF) could play an important pathophysiological role. Some studies have pointed to left atrial (LA) and left ventricular (LV) systolic and diastolic dysfunction as surrogate markers of AF. The aim of the study is to evaluate the relationship between echocardiographic parameters of LA and LV function, and the occurrence of AF revealed by continuous ECG monitoring in a cohort of patients with CS. Methods Single-center prospective cohort study. Seventy-two patients with CS with insertable cardiac monitors (ICM) underwent transthoracic echocardiography (TTE). TTE was focused on LA and LV function, including both standard and longitudinal strain-derived parameters. All detected AF episodes lasting more than 2 min were considered. Results Continuous ECG monitoring revealed subclinical AF in 23 patients (32%) at an average of 6.5 months after ICM implantation. Many echocardiographic parameters, indicating LA volume and LV systolic/diastolic function, were significantly associated with the occurrence of AF, suggesting the worst atrial function in the AF group. Furthermore, multivariable regression analysis revealed that peak atrial contraction strain and left ventricular strain were independently associated with AF (adjusted OR = 0.72, CI 95% 0.48–0.90, p = 0.005, and adjusted OR = 0.69, CI 95% 0.46–0.95, p = 0.041, respectively). Conclusion In patients with CS, LA and LV strain analysis add predictive value for the occurrence of AF over clinical and morpho-functional echocardiographic parameters. Impaired booster pump strain and LV longitudinal strain are strong and independent predictors of AF.